MODEL DECISION ANALYSIS IN DETERMINING BUILDING QUALITY BASED ON THE ANALYTICAL HIERARCHY PROCESS - Burhanuddin Burhanuddin; Emi Maulani; Veri Ilhadi (Multica Science and Technology, 2023)
Building infrastructure consisting of several types of alternatives that provide the need for selection of various kinds of assessments for ranking in carrying out repairs. The purpose of this study is to determine the priority order and condition of building quality, which is useful as a reference in improvement activities related to seeing the satisfaction of policy makers. Problems with building quality can result from various factors, one of which is related to facilities, building repairs and their handling which are feared to affect productivity in assessments and influence policy making. Primary data can be used as research data to be included in the decision model and direct observations can be made at the research location for each building in Dilhokseumawe. This study uses the Analytical Hierarchy Process (AHP) model, to determine the weight of the components obtained from the results of the interest assessment of building components which include the level of building damage, building age, ease of access, building structure, roof structure, building safety level. The results of the analysis show that factors the main consideration is improving the level of building security with a value of 0.297858847, the second ranking is the Building Structure factor with a priority value of 0.257685234%, the third ranking is the Ease of Access factor with a priority value of 0.128154963 and the Fourth is Building Age with a value of 0.076683671%. Finally the Roof Structure with a priority value of 0.072065172%. The results of this study can be used as recommendations for decision making in view of the quality of buildings and buildings.